Maktabgacha yoshdagi bolalarni maktabga tayyorlashda ingliz tilini axamiyati.: Maktabgacha yoshdagi bolalarni maktabga tayyorlashda ingliz tilini axamiyati. - Abdug’aniyeva, Iroda (Maktabgacha taʼlim jurnali, 2021)
To provide high-quality pre-school education, to radically improve the preparation of children for quality schooling, to introduce alternative programs in the educational process;